China officinalis as Possible Homeopathic Prophylaxis for the Brazilian Dengue Epidemic - Olandim, Ana Amélia Campos Claro; Fujino, Fernanda Maria Simões da Costa; Lemonica, Renata; Benites, Nilson Roberti; Barnabé, Vagner Doja (Homeopathy, 2024)
Dengue, a hyperendemic arbovirus thriving in tropical and sub-tropical climates globally, has seen a significant surge in Brazil over the past 5 years. Presently, the country faces an epidemic, posing a huge challenge to Public Health authorities due to the potentially lethal nature of severe infections. Based on Hahnemannian concepts and on the historically reported efficacy of homeopathy in fighting epidemics, this study aimed to provide supporting evidence for a homeopathic genus epidemicus approach to prevent severe forms of dengue. Symptoms related to the severe phase of the disease were prioritised in the repertorisation: China officinalis (Chin) received the highest total symptoms score (43 points from 21 symptoms) followed by Arsenicum album (31/13) and Phosphorus (29/14). In the asymptomatic population exposed to the etiological agent, the use of Chin might contribute as an additional strategy in the prophylaxis of dengue.
Keywords: dengue; homeopathy; prophylaxis; epidemic; China officinalis